2018
DOI: 10.3892/etm.2018.5932
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of risk factors for polycystic ovary syndrome complicated with non-alcoholic fatty liver disease

Abstract: The risk factors related to polycystic ovary syndrome (PCOS) patients complicated with non-alcoholic fatty liver disease (NAFLD) were investigated. A total of 188 PCOS patients treated in Shengli Oilfield Central Hospital (Dongying, China) from February 2014 to February 2015 were retrospectively analyzed as PCOS group, and PCOS group was further divided into NAFLD group and non-NAFLD (N-NAFLD) group according to the liver B ultrasound. In the same time-period, 65 healthy people were selected as normal control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
4
26
0
1
Order By: Relevance
“…In patients with NAFLd, triglyceride (TG) synthesis was identified to be increased compared with that of the TG export from the liver cells (10). Liver free fatty acids (FFAs) that are derived from circulating non-esterified fatty acids (NEFAs) are stored as TGs.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with NAFLd, triglyceride (TG) synthesis was identified to be increased compared with that of the TG export from the liver cells (10). Liver free fatty acids (FFAs) that are derived from circulating non-esterified fatty acids (NEFAs) are stored as TGs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications have proposed that low levels of SHBG are strongly associated with the features of metabolic syndrome [ 11 13 ] and may play an important role in modifying the risk of insulin resistance and its outcomes [ 14 16 ]. An inverse association between SHBG and the risk of NAFLD was observed in diabetic patients and women with polycystic ovarian syndrome [ 17 20 ]. Wang N et al also demonstrated that lower levels of SHBG were associated with the presence of NAFLD in Chinese men and menopausal women [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMI was significantly different (P < 0.01), and blood glucose showed a tendency to be different (P = 0.07) between the two groups. BMI, blood glucose, and testosterone are related to fatty liver [ 10 , 11 , 25 ]. Therefore, we set up two models for predicting elevated liver enzymes using receiver-operating characteristics (ROC) curves to determine clinical references for early diagnosis and prevention.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the identification of risk factors for NAFLD in PCOS is required to provide clinical references for early diagnosis and prevention. Several clinical measurements, such as age, body mass index (BMI), waist-to-hip ratio, obesity, triglyceride level, homeostatic model assessment for insulin resistance (HOMA-IR) index, and androgen level, are considered to be associated with NAFLD in women with PCOS [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%